Evaluation of the Effect of Propagation Models on a New Radio Resource Management Technique for Fifth Generation Mobile Systems (Damascus University Journal for engineering sciences, 2023)
Network designers are doing their best to develop technologies that provide communication services to anyone, anywhere, and anytime. Since the mobile traffic is expected to increase at Compound Annual Growth Rate (CAGR) of 46% from 2017 to 2022, the fifth generation (5G) of mobile communications is becoming a reality; which is supported multimedia applications for a wide range of requirements including: increased data rates, reduced latency, improved coverage, and increased energy efficiency. Achieving the objectives of the fifth generation requires the use of effective radio resource management techniques to ensure that priority is given to the requirements of different services. Current resource management techniques rely on scheduling algorithms that provide an optimal allocation of resources to ensure maximum flow rate, but do not take into consideration the characteristics of services such as video conferencing and their requirements.In this paper we propose a resource allocation algorithm that divides the applications into three groups according to the application requirements in terms of the data rate. We then evaluate the performance of this algorithm on a proposed fifth generation system that takes into account previous technologies such as LTE-A, Wi-Fi and WiMAX, as well as the latest technologies employed in the fifth generation, including mmWave connections and device to device (D2D) connections.
Keywords: 5G; D2D; mmWave; resource management; propagation models: Friis; Okumura Hata; Cost231